Sustained release of ubiquitin-like protein ISG-15 enhances tendon-to-bone healing following anterior cruciate ligament reconstruction in a mouse model - Yao, Jun-Cheng; Zhang, Jie-Xin; Wang, Xuan; Wu, Yu-Hao; Ke, Hao-Lin; Liang, Jia-Rong; Shao, Yan; Li, Jin-Tao; Liu, Yuan; Cai, Dao-Zhang; Pan, Jian-Ying (Frontiers in Bioengineering and Biotechnology, 2025)
The process of tendon-to-bone healing is regulated by several proteins and cytokines that play critical roles in shaping biomechanical properties and functional recovery. Among these, the ubiquitin-like protein ISG-15 has been reported to have a beneficial effect on tissue repair. However, its specific function in tendon-to-bone interface regeneration has not been well characterized. This study investigated the function of ISG15 in vitro and addressed its in vivo effects on tendon and bone healing. In this study, wild-type C57/BL6 mice underwent anterior cruciate ligament (ACL) reconstruction surgery, with a sustained-release hydrogel containing ISG15 protein injected into the bone tunnels in the treatment group. To assess its therapeutic potential, bone-tendon interface growth was evaluated through histological staining, while micro-computed tomography (Micro-CT) was employed to quantify newly formed bone and bone density within the bone tunnels. Additionally, biomechanical testing was performed to measure the mechanical strength of the grafted tendons, and immunohistochemistry was conducted to detect the expression of Runx2 and osteocalcin (OCN) at the bone-tendon interface. In vitro results showed that an appropriate concentration of ISG-15 has the ability to promote osteogenic differentiation of bone marrow mesenchymal stem cells. Also, In the in vivo experiments, the local application of ISG15 protein significantly reduced inflammatory tissue growth during the early stages of healing and minimized bone resorption in the later stages. Furthermore, Micro-CT analysis showed an increased volume of newly formed bone in the treatment group, while biomechanical testing demonstrated enhanced mechanical strength of the grafted tendons. In summary, this study suggests that the localized sustained release of ISG15 protein during ACL reconstruction facilitates tendon-to-bone interface repair by promoting bone ingrowth, ultimately leading to improved biomechanical properties and functional recovery.